Modelagem do efeito materno por meio de modelos de regressão aleatória - Lourenço, Daniela Andressa Lino (2011)
The aim of this study was to verify the influence of cows on the productive life of their progeny, according to the age of the cow when the records were measured. Data from Brazilian Association of Zebu Breeders (ABCZ) were used in two works. Formerly, it was observed the trend caused by age of dam (IVPE) on weight and on phenotypic variance of weight in Nellore beef cattle from birth until 385 days.A total of 2,882,824 body weight records from 1975 to 2009 were divided into five periods of measurement. The animal model was used and raising condition, contemporary group of herd-year-sex-birth season, and eleven classes of IVPE were considered as fixed effects.Based on this model, it was possible to reach the phenotypic variance and to verify the trends caused by IVPE. Data from 1976 to 2009 were used for the second work. A total of 293,742 body weight measures from 48,637 animals with average of 6.04 measurements per animal were applied to seven random regression models (MRA) and the coefficients of regression and estimated variances were compared. The MRA combined direct genetic and animal permanent environmental effect due age and, maternal genetic and maternal permanent environmental due IVPE and age of animal at measurement. In the first work, it was observed slightly quadratic trends of phenotypic variance for weight and body weight over IVPE. It shows that the age of dam at measurement have influenced the development of calves from birth to weaning, and it is source of phenotypic variance. In the second work, when the IVPE was considered as covariable for genetic and permanent environmental maternal effects in random regression models, it was observed that the partitioning of the phenotypic variance in genetic and environmental effects between animals and dams was not feasible. The coefficients of regression and the variances of genetic and permanent environmental maternal effects in function of IVPE showed either small values or standard errors greater than the estimates. Although the age of dam is an important effect for the development of the calf, mainly on early weights, the confusion observed between age of calf and IVPE as covariates during the estimation process indicated that the maternal effects could not be estimated in function of IVPE, for the models proposed by this study.